A case study of the European Starling Sturnus vulgaris as an introduction to discussion about causes and consequences of contact with nature deficiency among school children and teachers - Grzędzicka, Emilia (Studia Ecologiae et Bioethicae, 2017)
Outdoor activities are a part of education, but still remain a real challenge for teachers. In many cases, teachers do not have sufficient knowledge to conduct activities in this area. Moreover, younger school children usually did not have the opportunity for the contact with nature, so field activities are difficult for them. The answer to the shortage of outdoor activities in formal (school) education are the informal ones, conducted by naturalists gathered in external organizations and institutions. Using a case study as a way to raise awareness of important issues, in this paper the self-made study of European Starling Sturnus vulgaris observation was described. Starlings were feeding their chicks staying in tree nesting holes, during spring ornithological fieldworks with school children, organized in the Silesian Park. The person leading outdoor activities was watching the behavior of school children and teachers from many different groups. Observations collected as a case study help to understand the determinants and effects of the deficiency of contact with nature in children and adults.